Audit Partner’s Involvement in Audit Process, as an Indicator of Audit Quality - Vaicekauskas, Darius (Buhalterinės apskaitos teorija ir praktika, 2019)
Audit quality is determined by the criteria of the audit firm and the audit engagement team. One of the most important criteria of the audit engagement team is the involvement of the responsible engagement partner (hereinafter - partner) in the audit. As an executive of an audit firm, the partner is responsible for the quality control system within the audit firm, creating a "tone from the top" and presenting himself and his/her behavior, including involvement in the audit process, as an example for other less experienced audit engagement team members. This article examines the role of the partner in the audit engagement team structure to achieve audit quality, introduces the issue of partner involvement in the audit process, and proposes suggested indicators that can help assess the level of partner involement in the audit process for audit quality reviewers.
Keywords: Partner’s involvement in audit process; audit quality; audit engagement team